Cyclic ADP-Ribose Requires FK506-Binding Protein to Regulate Intracellular Ca2+ Dynamics and Catecholamine Release in Acetylcholine-Stimulated Bovine Adrenal Chromaffin Cells - Morita Katsuya; Kitayama Tomoya; Kitayama Shigeo; Dohi Toshihiro (Elsevier, 2006)
Abstract.: The present study was undertaken to elucidate whether cyclic ADP-ribose (cADPR) mediates the amplification of Ca2+ signaling and catecholamine release via the involvement of FK506-binding proteins (FKBPs)/ryanodine receptor (RyR) in bovine adrenal chromaffin cells. cADPR induced Ca2+ release in digitonin-permeabilized chromaffin cells and this was blocked by FK506 and rapamycin, ligands for FKBPs; 8Br-cADPR, a competitive antagonist for cADPR; and antibody for FKBP12/12.6, while it was enhanced by cyclosporin A. Ryanodine-induced Ca2+ release was not affected by 8Br-cADPR and was remarkably enhanced by FK506, rapamycin, cyclosporin A, and cADPR. FK506 binds to FKBP12.6 and removes it from RyRs, but cADPR did not affect the binding between FKBP12.6 and RyR. In intact chromaffin cells, 8Br-cADPR, FK506, and rapamycin, but not cyclosporin A attenuated the sustained intracellular free Ca2+ concentration ([Ca2+]i) rise induced by acetylcholine (ACh). 8Br-cADPR, FK506, and SK&F 96365 reduced the Mn2+ entry stimulated with ACh only when Ca2+ was present in the extracellular medium. 8Br-cADPR, FK506, and rapamycin concentration-dependently inhibited the ACh-induced catecholamine (CA) release. Here, we present evidence that FKBP12.6 associated with RyR may be required for Ca2+ release induced by cADPR in bovine adrenal chromaffin cells. cADPR-mediated Ca2+ release from endoplasmic reticulum in ACh-stimulated chromaffin cells is coupled with Ca2+ influx through the plasma membrane which is essential for ACh-stimulated CA release. Keywords:: cyclic ADP-ribose, FK506-binding protein, cytosolic Ca2+ dynamics, ryanodine receptor, catecholamine release